Luis Villoro's communitarianism and contemporary Marxism: contemporary debates on collectivism - Valerio Miranda, David (2024)
Luis Villoro's communitarianism and contemporary Marxism are theoretical proposals that in recent decades have continued to support the possibility of building human societies from a more collective sense, however, although both proposals are distinguished by defending collective society projects, they also preserve differences that give them identity and independence. In the current context, in which excessive individualistic selfishness is promoted by neoliberal capitalism, it is prudent to analyze other theories that propose alternatives to the political-economic and social precepts that are currently being implemented. In this way, carrying out a comparative analysis between the aforementioned collective proposals and contrasting them with the “culture of selfish individualism” of today's neoliberal societies is the objective of this article. Through this discussion, it is also intended to contribute to the current debates of Political Philosophy.